Self-Confidence and Logical Thinking as the Foundation of Academic Public Speaking for Students - Sholihah, Maidatus; Syaputra, Dewa Arif; Seena, Ismail; Ismawati, Ismawati (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Academic public speaking is an important competency for students, enabling them to convey scientific ideas, participate in discussions, and defend arguments rationally in a university environment. However, a common phenomenon shows that many students have adequate mastery of the material but experience difficulties in expressing it verbally. This article examines self-confidence and logical thinking as the main foundations of academic public speaking for students. This study uses a qualitative approach and a literature review, drawing on data from national and international journal articles, academic books, and relevant scientific proceedings published over the last 10 years. Data analysis used content analysis to synthesize research findings on affective and cognitive aspects of public speaking. The results of the study show that self-confidence increases the courage to speak and helps manage anxiety. At the same time, logical thinking patterns determine the clarity of arguments and the quality of responses in academic discussions. The important findings of this study confirm that effective academic public speaking requires integrating mental preparedness and an organized thinking structure. This article offers an integrative perspective and practical implications for strengthening students’ academic public speaking skills. The results of this study are important as a basis for designing more holistic learning strategies in higher education.